2017
DOI: 10.1016/j.expneurol.2017.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Sequential therapy of anti-Nogo-A antibody treatment and treadmill training leads to cumulative improvements after spinal cord injury in rats

Abstract: Intense training is the most clinically successful treatment modality following incomplete spinal cord injuries (SCIs). With the advent of plasticity enhancing treatments, understanding how treatments might interact when delivered in combination becomes critical. Here, we investigated a rational approach to sequentially combine treadmill locomotor training with antibody mediated suppression of the fiber growth inhibitory protein Nogo-A. Following a large but incomplete thoracic lesion, rats were immediately tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 49 publications
2
37
0
Order By: Relevance
“…33 For example, Chen et al found that treatment of rats with anti-NOGO-A antibodies after incomplete thoracic SCI followed by treadmill locomotive training improved motor recovery. 208…”
Section: Reproduced Withmentioning
confidence: 99%
“…33 For example, Chen et al found that treatment of rats with anti-NOGO-A antibodies after incomplete thoracic SCI followed by treadmill locomotive training improved motor recovery. 208…”
Section: Reproduced Withmentioning
confidence: 99%
“…How exactly rehabilitation influences plasticity is not well understood, however, appropriate rehabilitation regimes can prove to be astonishingly effective. For example, task-specific rehabilitation combined with ChABC almost completely restored some motor tasks (Chen et al, 2017;Garcia-Alias et al, 2009). Furthermore, specifically training the hindlimbs using bipedal treadmill exercise after thoracic spinal cord injury significantly improved several parameters of motor functions when combined with the plasticity-promoting treatment, anti-Nogo-A antibody (Chen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, task-specific rehabilitation combined with ChABC almost completely restored some motor tasks (Chen et al, 2017;Garcia-Alias et al, 2009). Furthermore, specifically training the hindlimbs using bipedal treadmill exercise after thoracic spinal cord injury significantly improved several parameters of motor functions when combined with the plasticity-promoting treatment, anti-Nogo-A antibody (Chen et al, 2017). Rehabilitation may enhance the ADAMTS4-induced improvements to behavioural scores that were shown by Tauchi and colleagues.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was observed once again that treatment with anti-Nogo followed by training was the most efficient strategy for increasing recovery after an incomplete thoracic lesion [43]. Climbing errors and paw dragging in rats were both reduced which is important as the CST is crucial in digit movement confirming its involvement in the recovery.…”
Section: Factors Affecting Outcome Of Therapymentioning
confidence: 91%